A Literature Survey On The Advances And Applications Of Artificial Neural Networks - Sai krishna kodali (AG Volumes, 2022)
As a branch of Artificial Intelligence, the Artificial Neural Network has been recognised as a novel computing technology. ANNs (Artificial Neural Networks) along with AI (Artificial Intelligence) are the topic of this study. Neural networks may be used with other computer technologies, such as fuzzy logic, to improve data interpretation capabilities. During the past two decades, artificial neural networks have been intensively explored and deployed as a key soft-computing technique. Pattern recognition, control, data analysis, and grouping are some of the most common uses of neural networks. High processing rates and the capacity to learn a solution to a problem from a group of samples are just two of the many qualities that Artificial Neural Networks have to offer. The primary goal of this study is to investigate the most current neural network applications and present an overview of the field in which ANNs are utilised and highlight the vital role that AI as well as NN played in many fields of research and development.